2014
DOI: 10.1103/physrevlett.112.040402
|View full text |Cite
|
Sign up to set email alerts
|

Many-Body Matter-Wave Dark Soliton

Abstract: The Gross-Pitaevskii equation -which describes interacting bosons in the mean-field approximation -possesses solitonic solutions in dimension one. For repulsively interacting particles, the stationary soliton is dark, i.e. is represented by a local density minimum. Many-body effects may lead to filling of the dark soliton. Using quasi-exact many-body simulations, we show that, in single realizations, the soliton appears totally dark although the single particle density tends to be uniform. [4][5][6][7][8][9].… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
67
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(74 citation statements)
references
References 36 publications
7
67
0
Order By: Relevance
“…Moreover, at times when the reduced one-body density, i.e. the average over many single shot measurements, has already relaxed to a flat distribution, the histograms of simulated destructive N -atom single shot measurements have revealed a soliton-like density minimum at random positions [34,36,[41][42][43]. These findings suggest the existence of highly non-trivial correlations being unravelled in single shot measurements.…”
Section: Introductionmentioning
confidence: 93%
“…Moreover, at times when the reduced one-body density, i.e. the average over many single shot measurements, has already relaxed to a flat distribution, the histograms of simulated destructive N -atom single shot measurements have revealed a soliton-like density minimum at random positions [34,36,[41][42][43]. These findings suggest the existence of highly non-trivial correlations being unravelled in single shot measurements.…”
Section: Introductionmentioning
confidence: 93%
“…1(b) and [9]). Observing numerically that |g 2 (0, 0) − 1| ≪ 1, we may now understand these non-local correlations as a generic property of parity-symmetric systems with essentially two oc-cupied NOs: Denoting the position of the soliton moving to the right/left with x R/L , our above results imply Second, in order to realize a situation with significant deviations of g 2 (0, 0) from unity, we additionally imprint a relative phase of π between the two half-spaces at t = 0 [6][7][8][9]. Thereby, a black soliton is initialized at x = 0.…”
Section: E Applicationsmentioning
confidence: 88%
“…e.g. [6][7][8][9]. Due to the increasing population of this orbital, the depth of the characteristic minimum in the reduced one-body density is reduced, i.e.…”
Section: E Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using time-dependent Bogoliubov theory [18][19][20] as well as more sophisticated numerical techniques [21][22][23][24][25] to treat the many-body dynamics of one-dimensional bosons at zero temperature, it has been shown that beyond-mean-field effects tend to deplete the condensate and to fill the soliton notch making dark solitons unstable. Here, however, we study theoretically the role of many-body correlations in determining relevant properties of gray solitons in a three-dimensional (3D) Bose gas, such as their excitation energy, density profile, and effective mass.…”
Section: Introductionmentioning
confidence: 99%